Causal ACTH-Depot Therapy during Pregnancies following Infertility Treatment - Rudolf Klimek; Marek Klimek; Peter Gralek; Dariusz Jasiczek (Hindawi Limited, 2012)
The aim of this paper was to confirm the efficacy of adrenocorticotropin depot (ACTH-depot) therapy in pregnancies with threatened miscarriage and preterm delivery through the desired stimulation of the adrenal glands controlled by the rest of organism. The activity of hypothalamic-pituitary-adrenal axis plays a key role in pregnancy. Such naturally stimulated endogenous corticosteroid hormones are free from unwanted side effects of their synthetics analogs. Low level of maternal blood ACTH and insufficient increase of induced by hypothalamic hormones oxytocinases (cystine-β-aminopeptidases) were indication to ACTH-depot therapy (0.5 mg/week) in our consecutive prospective studies. Contrary to antenatal use of synthetic corticosteroids, there are no temporal limits of this therapy, which has to be more often recommended into clinical prevention of fetal morbidity, treatment of premature delivery, and finally elimination of the newborn's mortality caused by the neuroendocrinological gestoses.